HEALTH LITERACY TENTANG KEPUTUSAN PROLIFE PADA REMAJA YANG MENGALAMI KEHAMILAN TIDAK DIKEHENDAKI - Kiky Ananda Yunitasari; Kismi Mubarokah (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
Unwanted Pregnancy in Indonesia is still high. Health literacy isÂ  crucial to decrease abortion numbers and unwanted pregnancy among adolescence. Its related with how to access information, to understand, to appraise and to apply the information. Good literacy effects adolescence avoid unsafe abortion and decide to keep their fetus This study used qualitative methods with a case study design on six main informants and five informants cross check. The data was collected by indepth interview and analyzed by thematic analysis. The results showed that the majority of informants get information from friends and midwives and they could understand those information. Only small number of informants who got information from internet because it used medical terminology.Most informants consider that the information from their friends and midwife were more credible.Â  Most of informants also apprised that abortion decision was a wrong way. So that, all of informants decided to choose prolife.The governmentand non-government organization should cooperate in giving education about the prevention of unwanted pregnancy and abortion. Good literacy of peers can avoid adolescencewho had pregnant to decide abortion. Keywords: Unwanted pregnancy, Prolife, Health Literacy